2016
DOI: 10.3892/or.2016.5288
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SOX18 promotes prostate cancer progression via the regulation of TCF1, c-Myc, cyclin D1 and MMP-7

Abstract: Sex determining region Y (SRY)-box 18 (SOX18) gene encodes transcription factors that have been recently confirmed to be overexpressed in various human types of cancer and maintain the malignant behavior of cancer cells. However, the role and its potential function in prostate cancer (PCa) has not been demonstrated and the mechanisms of SOX18 involved in tumor progression remain largely unclear. In the present study, the expression of SOX18 was analyzed in 98 PCa and 81 adjacent non-tumor tissues using immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Thus, future screening approaches in search of SOX18/PROX1 inhibitors are required and may reveal compounds with improved specificity. SOX18 overexpression is observed in different cancer types (12)(13)(14)(15)(16)(17)(18) causing enhanced migration, adhesion and invasivity (45). This underscores the importance to determine specific SOX18-targeting strategies (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, future screening approaches in search of SOX18/PROX1 inhibitors are required and may reveal compounds with improved specificity. SOX18 overexpression is observed in different cancer types (12)(13)(14)(15)(16)(17)(18) causing enhanced migration, adhesion and invasivity (45). This underscores the importance to determine specific SOX18-targeting strategies (20).…”
Section: Discussionmentioning
confidence: 99%
“…SOX18 directly regulates (among other target genes) the transcription of prospero homeobox protein 1 (PROX1), which itself determines the differentiation from blood vessels to lymphatic vessels during embryonic development (7)(8)(9)(10)(11). Furthermore, as SOX18 is overexpressed in various cancer entities (12)(13)(14)(15)(16)(17)(18), this additionally renders SOX18 a candidate target to block vascularisation and metastasis. Thus, a screening approach was undertaken to identify small molecules that inhibit SOX18.…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary studies have shown a disparity in the amount of SOX18 mRNA relative to the quantity of protein (25)(26)(27), which may be associated with the regulation of the translation by microRNAs (miRNAs). This has allowed us to hypothesize that the SOX18 transcript level is subject to control by miRNA molecules, since similar mechanisms are observed in many other types of tumors in relation to different types of proteins, as for example miRNA-34b in prostate cancer (28,29). miRNAs are involved in many important biological processes, such as proliferation, cell differentiation, apoptosis, embryogenesis and organogenesis.…”
Section: Introductionmentioning
confidence: 91%
“…MMP-7 (matrilysin) is the smallest proteinase from the entire metalloproteinases family with broad proteolytic activity against proteoglycans, elastin, laminin, collagens [19]. Overexpression and increased serum levels of this metalloproteinase have been confirmed in prostate, lung, renal, colorectal or breast malignancies [2024]. Some clinical studies have also revealed significantly elevated TIMP-1 levels in the plasma of patients with colorectal, prostate and pancreatic cancers, which was associated with worse clinical outcomes [25–27].…”
Section: Introductionmentioning
confidence: 99%